STRATEGI GURU BAHASA ARAB DALAM MENGATASI KESULITAN BERBAHASA ARAB SANTRI KELAS 1 KMI PONDOK PESANTREN MODERN AL SYAIKHABDUL WAHID KOTA BAUBAU - Rahman Selfara; Basri; La Jusu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the strategies employed by Arabic language teachers in overcoming Arabic language learning difficulties among first-grade KMI students at Pondok Pesantren Modern Al Syaikh Abdul Wahid, Baubau City, and to identify the factors contributing to the success of these strategies. The research employs a qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews, and documentation involving 2 Arabic language teachers and 32 first-grade KMI students. Data analysis followed the Miles, Huberman, and Saldaña model through stages of data condensation, data display, and conclusion drawing. The findings reveal that teachers implement five main strategies: daily vocabulary habituation, muhadatsah method, repetitive drills, creation of a bilingual environment, and continuous motivation. The success of these strategies is supported by five key factors including teacher competence and commitment, pesantren system support, the role of senior students as peer tutors, students' intrinsic motivation and family support, and integration of formal learning with informal practice. The research findings contribute to achieving SDG 4 on quality education through an effective Arabic language learning model that can be adapted by other Islamic educational institutions to enhance human resource quality in Arabic language proficiency and deep Islamic understanding.